Seasonal Fluctuations in Airway Responsiveness in Elite Endurance Athletes - Howard B Hemingson; Beth E Davis; Donald W Cockcroft (Canadian Respiratory Journal)
BACKGROUND: It has been suggested that exposure to winter training conditions (irritants in indoor facilities and/or cold, dry air in the outdoors) can increase airway responsiveness in elite endurance athletes.